Community structure analysis of family strombidae (Mollusca gastropoda) in four seagrass sites in Taklong Island National marine Reserve, Guimaras. - Magbato, Ellyza Dale G.
The community structure of Family Strombidae in four seagrass sites in Taklong Island National Marine Reserve (TINMR), Guimaras were characterized. Systematic plot sampling method was used to estimate Strombid density (d, in individuals per 100m2), species diversity and distribution. There were a total of 70 Strombid individuals collected by hand belonging to five species namely, Strombus labiatus Röding 1798, S. mutabilis Swainson 1821, S. aurisdianae Linnaeus 1767, S. luhuanus Linnaeus 1758, and S. urcerus Linnaeus 1758. Overall, there were significantly high densities of S. mutabilis (d=14) in studied seagrass meadows in TINMR, Guimaras. Three species were widespread (S. labiatus, S. mutabilis, S. luhuanus) found in all four sites. S. aurisdianae had the most limited distribution and encountered only in two sites. Among the study sites, Calaparan had the most number of species (d=347) and Piagau had the least number of species and had the least density (d=63).